'Sweet Ordering, Arrangement and Decision': The domestic nature of scientific illustration by women in the eighteenth and nineteenth centuries. Issue 2 (1st October 2014) - Rowe, Natalie
The eighteenth and nineteenth centuries saw many women pursue an interest in the natural sciences, particularly disciplines such as botany which were deemed suitable for their 'delicate minds'. However most women were not given the opportunity to practice their science as anything more than a feminine accomplishment. As a result women often remained amateurs, with the public sphere of professional science out of their reach.This article focuses on two women who attempted to pursue scientific careers as illustrators, but who also actively engaged with scientific research and made new and exciting discoveries. Exploring the lives and works of Maria Sibylla Merian (1647–1717) and Beatrix Potter (1866–1943) it is clear that they strived to work outside of their prescribed domain: the private sphere of the home.Through assessing the degree to which these women were confined by the ideals of domesticity and the practicalities of working within the private sphere, this article considers the effect of such constraints on their scientific practice and to what extent the domestic setting is reflected in their work. In fact it can even be argued that the domestic and decorative nature of their illustrations brought them greater success in the public sphere than their scientific endeavours and consequently secured them lasting popularity and esteem.